Risk performance indexes and measurement systems for mega construction projects - Kim, Seon-Gyoo (Journal of Civil Engineering and Management, 2010)
In recent years, interest in and studies on urban regeneration projects have increased. New urban regeneration projects, i.e., redevelopment projects, are being used to help solve the social and economic problems caused by antiquated buildings and degraded infrastructure. However, such projects can offer no performance guarantees because they have various and complex stakeholders and their huge scale exposes them to many risks. We propose a risk performance index to improve the efficiency of general performance measurement for mega projects by extending the existing cost/schedule‐based performance measurement system to include the risks of such mega projects. The risk performance index method proposed in this study is similar to the conventional EVMS and makes it possible to perform a three‐dimensional integrated performance measurement of cost/schedule/risk through 18 indexes and variables. First Published Online: 10 Feb 2011